1995
DOI: 10.1007/bf02306569
|View full text |Cite
|
Sign up to set email alerts
|

The public's perception of psychotherapy and counseling: Differential views on the effectiveness of psychologists, psychiatrists, and other providers

Abstract: This study examined the public's perceptions relative to the effectiveness of psychotherapy and counseling, expectations of treatment efficacy for different PERCEPTION OF RELATIVE EFFICACY AMONG PROVIDERSIn most states, psychiatrists, clinical psychologists, counseling psychologists, counselors, marital and family therapists, and social workers are licensed to provide mental health services and are reimbursed by third party

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Consistent with the findings of Richardson and Handal (1995), the students in the current study did not perceive MFTs to be involved-or particularly qualified-as mental health professionals who are capable of diagnosing and treating mental disorders. The most immediate implication with regard to this finding is that significant work is needed to educate the general public, especially students, about the identities and qualifications of MFCs or MFTs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the findings of Richardson and Handal (1995), the students in the current study did not perceive MFTs to be involved-or particularly qualified-as mental health professionals who are capable of diagnosing and treating mental disorders. The most immediate implication with regard to this finding is that significant work is needed to educate the general public, especially students, about the identities and qualifications of MFCs or MFTs.…”
Section: Discussionsupporting
confidence: 91%
“…According to Richardson and Handal (1995), consumers have supposed that psychiatrists, clinical psychologists, and counseling psychologists would be capable of handling the most severe disorders, while professional counselors were thought to be capable of handling moderately severe cases of psychiatric disorders. MFCs or MFTs, however, were perceived to be specifically capable only in addressing therapeutic issues pertaining to marriages and the family, and self-help groups were thought to be the most effective with drug and alcohol treatments.…”
mentioning
confidence: 99%
“…Psychologists were rated as the third most preferred, and fourth most qualified, providers of weight loss support, and as trustworthy and helpful in lifestyle intervention. They were exceeded only by other specialist services, that is dietitians, exercise physiologists and weight loss consultants, which is a trend reported in other research on service provider preferences (Angermeyer et al, 2017;Richardson & Handal, 1995). Psychologists were also more highly endorsed than GPs, reflecting findings in the mental health context (Angermeyer et al, 2017), and perhaps the view that GPs may be perceived as having comparatively less time to offer weight management support (Tan et al, 2006).…”
Section: Discussionmentioning
confidence: 67%
“…However, ratings of psychologists in this study were also similar to the findings of Tol et al (2014) with respect to dietitians. To minimise this potential bias in future studies, forced‐choice options could be employed, or rankings of professionals or services (Hansson et al, 2010), to account for the general preference for specialists reported in past studies (Angermeyer et al, 2017; Richardson & Handal, 1995). In addition, a broader range of specialist health professionals (e.g., psychiatrists and endocrinologists) and other providers (e.g., personal trainers) would be valuable to include in future studies to gain a stronger understanding of attitudes towards the broad range of providers working this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation